2012
DOI: 10.1128/ec.00145-12
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Cell Division Cycle in Trypanosoma brucei

Abstract: The cell division cycle is tightly regulated by the activation and inactivation of a series of proteins that control the replication and segregation of organelles to the daughter cells. During the past decade, we have witnessed significant advances in our understanding of the cell cycle in Trypanosoma brucei and how the cycle is regulated by various regulatory proteins. However, many other regulators, especially those unique to trypanosomes, remain to be identified, and we are just beginning to delineate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 122 publications
(156 reference statements)
0
65
0
Order By: Relevance
“…Trypanosomes initiate cytokinesis from the anterior tip of the new FAZ filament, and it is believed that the regulators playing direct roles in cytokinesis initiation should localize to the new FAZ tip before cytokinesis initiation (21). CIF1 is the fifth protein, after TbAUK1 (12), TbCPC1 (12), TbCPC2 (12), and TbPLK (22), that concentrates at the new FAZ tip, and our RNAi studies demonstrated that CIF1 is essential for cytokinesis initiation from the anterior tip of the new FAZ filament (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Trypanosomes initiate cytokinesis from the anterior tip of the new FAZ filament, and it is believed that the regulators playing direct roles in cytokinesis initiation should localize to the new FAZ tip before cytokinesis initiation (21). CIF1 is the fifth protein, after TbAUK1 (12), TbCPC1 (12), TbCPC2 (12), and TbPLK (22), that concentrates at the new FAZ tip, and our RNAi studies demonstrated that CIF1 is essential for cytokinesis initiation from the anterior tip of the new FAZ filament (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, cyclin-dependent kinases in general are considered to be among the most promising drug targets, due to their key function in cell proliferation (61). Accordingly, CRK9 silencing has been shown to affect trypanosome mitosis and cytokinesis (42,62).…”
Section: Discussionmentioning
confidence: 99%
“…Ancestral eukaryotes evolved origin recognition complexes (ORCs) more complex than the single protein Cdc-6 of archaebacteria, probably because the suddenness of mitotic anaphase (rapidly segregating all parts of chromosomes at once, unlike the temporally separate segregation of origins and the generally single terminus in bacteria) required concerted replication initiation at hundreds of origins, ensuring replication completion and tighter chromosome folding (using extra histones and novel heterochromatin machinery: Cavalier-Smith 2010c) well before mitosis; uniquely in eukaryotes, mitosis demands a temporally discrete S phase. Formerly, only neokaryotes were thought to have ORCs (Cavalier-Smith 2010b), but extremely divergent versions of most constituents are now known in trypanosomes, whose cell-cycle controls are the most divergent within eukaryotes (Li 2012), consistent with eukaryotic rooting between Euglenozoa and neokaryotes ( Figs. 1 and 3).…”
Section: The Neomuran Revolution and Origin Of Eukaryotesmentioning
confidence: 99%
“…Successively more complex controls and checkpoints evolved with novel polo-like and aurora S/T kinases playing multifarious roles in mitosis and cytokinesis and a multiplicity of kinesins evolving to improve spindle assembly and function. Probably all proteins shared by trypanosomes (Li 2012) and opisthokonts evolved before the eukaryote cenancestor. Mitosis (upper panel) was converted to meiosis by two innovations (lower panel): homologous chromosome pairing by the synaptonemal complex and blocking centromeric cohesin digestion at meiosis 1 anaphase, which automatically bypassed cell-cycle resetting caused by anaphase centromere splitting so that the next interphase had no S phase as previously explained (Cavalier-Smith 1981), thereby halving ploidy-the original meiotic function (Cavalier-Smith 2002a, 2010c.…”
Section: The Neomuran Revolution and Origin Of Eukaryotesmentioning
confidence: 99%